Format Cetak vs Digital: Preferensi Membaca Bahan Bacaan Akademik Mahasiswa Pascasarjana Universitas Indonesia - Doan Ilman Munandar (Pustakaloka, 2019)
Reading media as tools to convey information has undergone physical radical changes. Since the invention of the printing press in the 15th century, until the digital revolution in the 1980s, the habits of reading people have undergone many changes. In the past people had to buy reading media in print, nowadays only by downloading files in digital format, someone can already do reading activities on cellphones, tablets, and computers. No exception for the habit of reading academic material on students, several studies show a tendency for student preferences in reading academic material in digital format rather than in printed format. This study examined the preferences of the graduate students in University of Indonesia in reading academic reading materials such as textbooks and scientific journals. An online questionnaire used to collect data and 68 graduate students participated in this study.The results of the study show that although postgraduate students prefer digital formats, the print format is more convenient and make them more focused on reading.